PENGARUH LOAN TO DEPOSIT RATIO DAN CAPITAL ADEQUACY RATIO SERTA TINGKAT BUNGA KREDIT TERHADAP NON PERFORMING LOAN (NPL) PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011- 2016 - Sahputra, M. Qodrat; Bone, Hamid; Setiawati, Ledy (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This study aims to determine the significance of the effect of Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Loan Interest Rate to Non Performing Loan (NPL) at PT Bank Rakyat Indonesia Persero Tbk 2011-2014 period. Data obtained from the official website publication Bank Rakyat Indonesia (BRI) Period 2011-2016.Analytical methods used in this research are Normality Test, Autocorrelation Test, Multicolonierity Test, Heteroskedasticity Test, Coefficient of Determination Test R2, Model Feasibility Test (F Test), Statistical Test t, and Analysis of Multiple Linear Regression. The data used are quarterly financial statements at Bank Rakyat Indonesia Persero Tbk period 2011 - 2016.The results showed that the data is normally distributed. Furthermore, based on the statistical test results found no variables that deviate from the classical assumption test. The result of this research shows that Loan To Deposit Ratio (LDR) variable has positive and significant influence to Non Performing Loan (NPL). Capital Adequacy Ratio (CAR) variable has positive and not significant influence to Non Performing Loan (NPL). While the variable of Interest Rate of Credit has a positive and significant influence to Non Performing Loan (NPL). Based on the Determination Coefficient Test Result R2, Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) and Credit Interest Rate have influence of 66, 2%, while the rest of 33.8% influenced by other factors not examined in this study. Keywords :Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Tingkat Bunga Kredit, Non Performing Loan (NPL).